Inhibition of LSD1 reduces herpesvirus infection, shedding, and recurrence by promoting epigenetic suppression of viral genomes - Hill, James M; Quenelle, Debra C; Cardin, Rhonda D; Vogel, Jodi L; Clement, Christian; Bravo, Fernando J; Foster, Timothy P; Bosch-Marce, Marta; Raja, Priya; Lee, Jennifer S; Bernstein, David I; Krause, Philip R; et al. (Science translational medicine, 2014)
Herpesviruses are highly prevalent and maintain lifelong latent reservoirs, thus posing challenges to the control of herpetic disease despite the availability of antiviral pharmaceuticals that target viral DNA replication. The initiation of herpes simplex virus infection and reactivation from latency is dependent on a transcriptional coactivator complex that contains two required histone demethylases, LSD1 (lysine-specific demethylase 1) and a member of the JMJD2 family (Jumonji C domain-containing protein 2). Inhibition of either of these enzymes results in heterochromatic suppression of the viral genome and blocks infection and reactivation in vitro. We demonstrate that viral infection can be epigenetically suppressed in three animal models of herpes simplex virus infection and disease. Treating animals with the monoamine oxidase inhibitor tranylcypromine to inhibit LSD1 suppressed viral lytic infection, subclinical shedding, and reactivation from latency in vivo. This phenotypic suppression was correlated with enhanced epigenetic suppression of the viral genome and suggests that, even during latency, the chromatin state of the virus is dynamic. Therefore, epi-pharmaceuticals may represent a promising approach to treat herpetic diseases.